Challenging removal of a knotted nasogastric tube following insertion under general anaesthetic. Issue 10 (29th October 2020) - Conroy, Michael; Wichmann, Katherine; Farkas, Nicholas; Di-Nicola, Valerio
Abstract : A 74-year-old man presented with acute small bowel obstruction secondary to recurrence of a caecal tumour. The patient underwent laparotomy and formation of loop ileostomy and had a nasogastric tube (NGT) inserted in the theatre. A decision was made to remove the patient's NGT postoperatively, which was found to be stuck. High-quality imaging demonstrated a knot in the tube within the nasopharynx; so, subsequent removal via the oral route necessitated sedation. This case highlights the importance of considering rare or unusual complications of NGT insertion when a patient describes more pain or discomfort than would otherwise be expected. The clarity of imaging highlights clearly the underlying findings when compared with the few other documented cases. We offer a number of learning points specific to this complication.